GROWTH FACTOR LOADED FUNCTIONALIZED GOLD NANOPARTICLES AS POTENTIAL TARGETED TREATMENT FOR ACUTE RENAL FAILURE - Zayed, Gamal M.; El-feky, Gina S. (International Journal of Applied Pharmaceutics, 2019)
Objective: Gold nanoparticles (GNPs) have been synthesized and functionalized with chitosan alkanethiol polyethylene glycol as a renal targeting ligand (CS-PEG-AlkSH-GNPs) and finally loaded with insulin-like growth factor-I (IGF-I) for selectively and effectively treating acute renal failure. Methods: In this study, GNPs were prepared and characterized using transmission electron microscopy, photon correlation spectroscopy and inductively coupled plasma (ICP-OES). The surface of the GNPs was further decorated using synthesized CS-PEG-Alk-SH and IGF-I. IGF-I loaded CS-PEG-ALK-SH-GNP were characterized for their growth factor loading capacity, particle size, zeta potential and dispersion stability. In vitro release profile and bioactivity of IGF-I from IGF-I loaded CS-PEG-AlkSH-GNPs were assessed using cell culture technique. Biological distribution, pharmacokinetic investigation and toxicity study of IGF-I loaded CS-PEG-AlkSH-GNPs were carried out using experimental animals. Results: The size of GNPs was less than 50 nm with a surface charge of about-45 mV. Coating GNPs with CS-PEG-Alk-SH acquired the particles high in vitro stability in 5 M NaCl and bovine serum albumin (BSA). The assembly's bioactivity was tested on cell culture and the released IGF-I was found to maintain bioactivity equivalent to its released percentage. When tested on mice, IGF-I loaded CS-PEG-ALK-SH-GNP reached a concentration of 60% in 6 h time in the kidneys with an elimination half-life higher than that of the control GNPs indicating efficient renal residence and targeting processes. The system was proved nontoxic. Conclusion: CS-PEG-AlkSH-GNPs could represent an efficient tool for the targeted delivery of growth factors and other biomolecules to the kidneys. Â